Cohort fertility, parity progression, and family size in former Yugoslav countries - Ivan Čipin; Kryštof Zeman; Petra Meimurec (Comparative Population Studies (CPoS), 2020)
Yugoslavia was a union of countries at the crossroads of cultures, rich in diversity, bringing together heterogeneous populations with very different demographic transition pathways, particularly with respect to fertility. This paper studies the trends and patterns of cohort fertility in former Yugoslav countries, similarities and differences between the countries, and their possible clustering. Do former Yugoslav countries exhibit persistent diversity to this day, or is there convergence in terms of cohort fertility behaviour? If so, what might account for this homogeneity within Yugoslavia's heterogeneity? We trace how fertility behaviour changed from the turn of the twentieth century, when Yugoslav countries began their progression from agrarian into industrial capitalist societies. We consider the factors related to a rapid transformation to socialist modernity after 1945 and proceed to investigate the federation's breakup and the successor states' transitions to market economies in the early 1990s. Our study thus covers a century of socioeconomic and fertility developments within the region. We analyse census data on children born by means of the completed cohort fertility rate, parity progression ratios, and parity composition. Our results show that while fertility levels decreased in all former Yugoslav republics, this happened at different speeds and taking different paths. Parity progression to higher birth orders was particularly responsible for this development, as well as for the differences and similarities between the respective republics. Former Yugoslav republics are clustered into three groups, where Croatia, Slovenia, and Serbia form the low fertility group, and Bosnia-Herzegovina, North Macedonia, and Montenegro belong to a higher fertility group. Kosovo remains a special case with exceptionally high fertility in the European context. We conclude that this clustering stems from a complex interplay of historical, political, economic and social factors.
urn:nbn:de:bib-cpos-2020-18en0
Keywords: 300; Cohort fertility; Census data; Former Yugoslav countries; Parity progression ratios; Parity composition